An Optimal and Flexible Approach for Drought Quantification Based on Standardised Indices - Sergio M. Vicente‐Serrano; Fergus Reig; Santiago Beguería; Ahmed El‐Kenawy; Fernando Domínguez‐Castro; Magí Franquesa; Luis Gimeno‐Sotelo; María Adell‐Michavilla; Amar Halifa‐Marín; Iván Noguera; Miguel Andres‐Martin; Cesar Azorin‐Molina; et al. (International Journal of Climatology, 2025)
In this study we propose a novel approach to standardising drought indices that offers flexibility tailored to local conditions. This involves employing different probability distributions and the Akaike Information Criterion to identify the most appropriate distribution for each region and variable. Following this approach, our proposed methodology enhances the accuracy and comparability across different spatial and temporal scales, with improved representation of extreme drought events. Nonetheless, despite the increased computational requirements associated with this approach, the advantages are substantial. By enhancing accuracy, comparability and adaptability, it may improve drought monitoring and management practices. Moreover, the methodology provides a versatile framework for standardising a wide range of environmental variables beyond traditional drought indices, and software for calculations is provided ( https://github.com/lcsc/FlexDroughtIndex ). Overall, the findings of this study can advance drought assessments by providing an innovative and flexible methodology that addresses key limitations of current approaches.